Gastric CD56-negative Extranodal Natural Killer/T-cell Lymphoma: A Case Report - Joohong Chung; Sam Ryong Jee; Eunjeong Choi; Seung Jung Yu; Jun Sik Yoon; Hong Sub Lee; Sang Heon Lee; Sung Jae Park; Ha Young Park (The Korean Journal of Gastroenterology, 2024)
Extranodal natural killer (NK)/T-cell lymphoma, nasal type (ENKTCL-NT) is the most common subtype of Epstein-Barr virus-associated NK/T-cell lymphomas. ENKTCL-NT occurs infrequently in the gastrointestinal tract. In particular, reports of ENKTCL-on NT arising from the stomach are extremely rare. Several clusters of differentiation (CDs) have been useful in recognizing NK-cells, T-cells, and tumor cells of NK/T-cell lymphomas. Among them, the CD56 antigen is considered the most sensitive marker for ENKTCL-NT and is expressed in almost all cases of ENKTCL-NT. Thus, the development of CD56-negative ENKTCL-NT is highly atypical. This paper reports a case of a young Asian female who presented with gastric ulcer bleeding. The patient was histologically diagnosed with ENKTCL-NT. No tumor cells for CD56 were observed, whereas no monoclonality of the T-cell receptor gamma gene rearrangement was detected in the tumor cells. The patient was scheduled for systemic chemotherapy six times and achieved complete remission. Peripheral blood-hematopoietic stem cell transplantation was performed later.